The wisdom of order: an exploration of Lonergan's method in theology - Dadosky, John Daniel (Lonergan Studies, 2024)
In 1972, renowned Canadian philosopher and theologian Bernard Lonergan published Method in Theology. Now, following the fiftieth anniversary of his landmark work, The Wisdom of Order presents the next step in advancing the thought of this significant religious theorist. In addition to the previously compiled Collected Works of Bernard Lonergan, this book aims to provide an appreciation and exploration of Method in Theology. It analyses the first five chapters of the work with commentaries to help readers traverse Lonergan’s thought more effectively and deeply. John D. Dadosky presents compelling exposition and observations to assist readers. The book explores questions related to the philosophical status of beauty, which Lonergan does not address. In addition to Lonergan’s three stages of meaning, the book also seeks to develop a fourth stage that pertains to the turn to alterity emphasizing positive relations with other cultures and religions. As a result, The Wisdom of Order critically analyses an important groundbreaking work while also highlighting areas for further development